Pengaruh Dimensi Profesionalisme Auditor Terhadap Pertimbangan Tingkat Materialitas Dalam Proses Pengauditan Laporan Keuangan - Putri, Diah Utami; Diana, Nur; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
SA 320 stated that the determination of the materiality needs professional auditor considerations. The components of auditor professionalism consists of dedication to one’s profession, social obligation, independence, belief in profession, and having friendly relationships with colleague. This research aims to analyze the factors influencing the auditor’s considerations of materiality for finacial statement audit such as dedication to one’s profession, social obligation, autonomy demands, belief in profession and having friendly relationships with colleague. The data of this research was collected through questionnaires that were distributed to 35 auditors in Public Accountant Office of Malang city as the respondents and also the method that being used in this research is multiple regression analysis with the help of SPSS 25. The results of this research show that dedication to one’s profession, belief in profession, have positive influences on the auditor’s consideration of materiality for financial statement audit. Based on the results, it can be concluded that to determine the level of materiality properly for financial statement audit, there are several thing that needs to be considered such as dedication to one’s profession, social obligation, independence, belief in profession, and also having friendly relationships with colleague.Keywords: professionalism, materiality